Beneficial effects of Teucrium polium hydroalcoholic extract on letrozole-induced polycystic ovary syndrome in rat model - Zeynab Khosrowpour; Shirin Fahimi; Fateme Jafari; Mojgan Tansaz; Shamim Sahranavard; Mehrdad Faizi (Korean Society of Obstetrics and Gynecology, 2023)
Objective Polycystic ovary syndrome (PCOS) is an endocrine disorder that disrupts the menstrual cycle and causes infertility. Considering the increasing use of medicinal plants, the present study aimed to evaluate the effects of Teucrium polium L. on letrozole-induced PCOS in female rats. Methods Six groups of rats (n=7 each) were evaluated. The control group received 1% carboxy methyl cellulose as vehicle, while the five other groups received letrozole 1 mg/kg orally for 21 days. After PCOS induction, the rats were orally administered T. polium extract (50, 100, and 200 mg/kg) or metformin (200 mg/kg) for 28 days. Subsequently, body and ovarian weights and serum levels of follicle stimulating hormone, luteinizing hormone (LH), estradiol, progesterone, and testosterone were measured. Finally, the ovarian tissues were isolated for histological examination. Results There were no significant changes in weekly body weight in any group. After 21 days of letrozole administration, PCOS induction was confirmed by estrous cycle irregularities and increased LH and testosterone levels. After treatment with the hydroalcoholic extract of T. polium, testosterone and LH levels were significantly reduced in all groups (P<0.05). Histological studies of ovaries in the metformin and T. polium groups exhibited normal follicular development with fewer and smaller cystic follicles than those in the PCOS group. Conclusion The hydroalcoholic extract of T. polium improves serum levels of sex hormones, restores ovarian morphology in PCOS-induced rats, and is a good candidate for further clinical trials.